Recognizing Allogenic Controls on the Stratigraphic Architecture of Ancient Alluvial Fans in the Western US - Meek, Scott R.; Carrapa, Barbara; DeCelles, Peter G. (Frontiers in Earth Science, 2020)
Alluvial fans are a significant part of the sediment routing system, forming distinctive steep, fan-shaped deposits of coarse-grained detritus where rivers lose flow velocity after exiting confined mountain drainages. Processes on the fan are influenced by both internal (autogenic) feedback cycles like channel avulsion and by external (allogenic) conditions such as climate and tectonics. These conditions in turn influence the stratigraphic architecture (i.e., the pattern of channel stacking and sizes) within the fan. Studying stratigraphic architecture of alluvial fans can, therefore, provide insight into controls on fan deposition. We employ UAV-based photogrammetric models to analyze the stratigraphic architecture of two well-exposed ancient alluvial fans in the western US – the Eocene Richards Mountain Conglomerate and the Cretaceous Echo Canyon Conglomerate. Both fans were deposited under relatively warm, wet climates and compressional tectonic regimes. We use a seven-fold hierarchy of bounding surfaces and associated lithosomes to describe alluvial fan architecture. First- through fourth-order surfaces and lithosomes represent bedform to channel-scale features influenced primarily by autogenic processes on the fan. Controls on fifth-order surfaces/lithosomes have historically been poorly understood, but probably represent fanhead trench migration and lobe construction. Sixth-order surfaces bound individual alluvial fans and seventh-order surfaces correspond to formation boundaries. These are controlled primarily by tectonics. The fifth-order architectural style of the deposits in our two study areas is significantly different and we use this difference to try to isolate a primary control on fifth-order alluvial architecture. Average width:height ratios of fifth-order lithosomes are nearly twice as high for Echo Canyon (112:1) than for Richards Mountain (64:1). This indicates that active channels on the Echo Canyon fan were more mobile than those on the Richards Mountain fan. We attribute this to a more seasonal climate and less vegetation during the deposition of the Echo Canyon Conglomerate. This would have increased lateral migration by destabilizing channels through increased sediment flux and flood events. Our results imply that fifth-order stratigraphic architecture of ancient alluvial fans may provide insight into allogenic processes related to paleoclimate. They also indicate risk of increased geologic hazards on alluvial fans where anthropogenic climate change increases future climate variability.